PENGARUH KUALITAS PELAYANAN DAN CITRA TERHADAP KEPUASAN MAHASISWA PADA AKADEMI KEBIDANAN AISYIYAH PONTIANAK - Nurmalasari Nurmalasari (Jurnal Khatulistiwa Informatika, 2014)
This study discusses the influence between service quality and image of student satisfaction in Midwifery Academy Aisyiyah Pontianak. More specifically, the objectives of this study were 1) To determine the effect of service quality on student satisfaction Midwifery Academy Aisyiyah Pontianak, 2) To determine the effect of imagery on student satisfaction Midwifery Academy Aisyiyah Pontianak, 3) To determine the effect of service quality and image of the Midwifery Academy student satisfaction Aisyiyah Pontianak.The population in this study are all active students of the Academy of Midwifery Aisyiyah Pontianak, amounting to 422 people. The samples using stratified random sampling method Proportionated. Withdrawal number of samples using the formula Slovin and samples obtained in this study as many as 81 people. This study used a multiple linear regression analysis with the application of statistical software Special Package for Science (SPSS) version 17.0. The results showed that: 1) The quality of service and a significant positive effect on student satisfaction Midwifery Academy Aisyiyah Pontianak, 2) image is positive but not significant effect on student satisfaction Midwifery Academy Aisyiyah Pontianak, 3) quality of service and image (simultaneously) and the positive effect exhibited significantly to student satisfaction Midwifery Academy Aisyiyah Pontianak, amounting to 51.3% which means that the quality of service and the image has a significant effect on satisfaction. And the remaining 48.7% is influenced by other factors not addressed in this study.Keywords: Quality of Service, Image and Satisfaction